Incorporating baseline functional status to improve validity of neurological outcome assessments following cardiac arrest. (September 2019) - Eng, Kevin J.; Yang, Jenny Z.; Tyagi, Sanjeev; Odish, Mazen F.; Rosen, Sheri; Sell, Rebecca E.; Beitler, Jeremy R.
Abstract: Background: Neurological status at hospital discharge is routinely used to assess patient outcome after cardiac arrest. However, attribution of impairment to the arrest is valid only if baseline neurological status is known. This study evaluated whether incorporating baseline neurological status improves performance of a widely employed neurological outcome scale for quantifying arrest-attributable morbidity. Methods: Retrospective cohort study of two U.S. hospitals. Neurological function was assessed via Cerebral performance category (CPC), an ordinal five-point scale with 1 indicating sufficient cognition to lead an independent life and 5 representing brain death. Hospitalized adult patients who suffered in-hospital cardiac arrest for which cardiopulmonary resuscitation was attempted between 2011–2015 were included. Patients were identified through a quality improvement registry that captures all inpatient arrests in the two hospitals. Results: Of 486 patients who suffered in-hospital cardiac arrest, 124 (25.5%) had baseline abnormal neurological function (pre-hospitalization CPC>1). Although 54 patients had a normal discharge CPC of 1, 80 patients had no change in CPC from their prior baseline (11.1% vs. 16.5% met criterion for "normal" outcome defined as CPC of 1 vs. change-in-CPC of 0; McNemar p < .01; kappa for agreement: .78, 95% CI .69–.86). Across several formulations of criteria for "good" neurological outcome, similar discordance existed between conventional definitions considering only discharge CPC and modified definitions that included change-in-CPC from baseline. Conclusions: Incorporating change-in-CPC into criteria for "good" neurological outcome post-arrest yields discordant results from traditional approaches that consider discharge CPC only and increases face validity of reporting arrest-related morbidity.